Decision support system for determination Head of Study Program with analytic network process method - Br Tarigan, Nera Mayana; Marpaung, Meman; Rangita, Gayatri; Maduri, Maduri (Politeknik Ganesha Medan, 2022)
Changes in management in institutions are common, but in making changes, it is better to use an analysis with the application of technology and methods used in the application. In structural management changes, especially at the head of the study program, it is still very common to make direct appointments. This can result in errors in making selections and cause problems of ignorance, lack of productivity. So it is appropriate to build an application by applying the method as an analysis. This study aims to analyze the determination of the head of the study program by applying the Analytic Network Process Method, designing and building a decision support system for the determination of the head of the study program. The Analytic Network Process method is used to analyze in determining the head of the study program based on criteria, this decision support system is built on a web-based basis. The research method is the survey research method, which is a survey research method. This is a research method conducted using surveys or collecting data through research respondents. This research is targeted to assist the management in determining the head of the study program. The results of the research that the highest value is 0.18856 followed by 0.15252, 0.05329, 04582, 0.032110, 0.02770 in the limit matrix table.